Biocatalytic Phosphorylations of Metabolites: Past, Present, and Future. Issue 5 (May 2017) - Wohlgemuth, Roland; Liese, Andreas; Streit, Wolfgang
Abstract : Phosphorus is a key element for life that occurs in living cells as a structural part of many key biochemicals. Phosphorus plays important functional roles in biocatalysis, such as making metabolic reaction steps irreversible by transferring energy-rich groups, using phosphate groups as leaving groups, or selectively hydrolyzing phosphorus–oxygen or phosphorus–nitrogen bonds. The large number of biocatalysts known to catalyze the transfer of phosphorus-containing groups from donor molecules to acceptor molecules covers a wide variety of reaction classes. Bioprocessing technology can and should replicate these naturally occurring reactions. We illuminate some strategic advantages of this promising technology for developing biocatalytic processes and separation steps. Constraints, opportunities, and outlooks for implementing green engineering procedures to establish sustainable production processes are discussed. Trends: A large number of phosphoryl group-transferring enzymes can be utilized for mild biocatalytic phosphorylation reactions of metabolites without protecting groups and with high chemoselectivity, regioselectivity, and enantioselectivity. Fast and sensitive analytical methodologies with high information content have been developed and are essential for functional assays and real-time monitoring of biocatalytic phosphorylation reactions. Enzyme functions, properties, and structures for known phosphoryl group-transferring enzymes, their relations, and substrate scope are of increased interest and can be used as a starting point for extending their applications and properties. Best practices in the overall design of biocatalytic phosphorylation processes, reaction engineering, and product recovery assist in the translation to industrial biotransformations.